2020
DOI: 10.3390/nu12103201
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Characteristics and Its Association with Daily Micronutrients Intake in Children and Adolescents–A Systematic Review and Meta-Analysis

Abstract: Breakfast is an important source of key nutrients in the diet. For this reason, the aim of this review was to investigate the associations between breakfast consumption and daily micronutrients intake in both children and adolescents (aged 2–18 years). A peer-reviewed systematic search was conducted in three datasets (PubMed, Scopus and Cochrane Library) in February 2020 in English and Spanish. Two independent reviewers evaluated 3188 studies considering the AXIS critical appraisal and PRISMA methodologies. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 82 publications
0
33
0
1
Order By: Relevance
“…It is well known that a high-quality breakfast is a great source of amino acids, vitamins, minerals, antioxidants, and fiber, which positively impacts children’s global health and cognition [ 5 , 6 , 7 ]. In this way, evidence indicates that breakfast composition may affect behavior, cognition, and learning in children and adolescents [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that a high-quality breakfast is a great source of amino acids, vitamins, minerals, antioxidants, and fiber, which positively impacts children’s global health and cognition [ 5 , 6 , 7 ]. In this way, evidence indicates that breakfast composition may affect behavior, cognition, and learning in children and adolescents [ 47 , 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, dairy in breakfast has an important role on improving growth and brain function in school-age children [ 16 ]; indeed, fortified milk could be an effective way to obtain polyunsaturated fatty acids, a crucial nutrient favouring brain development [ 58 ]. Furthermore, dairy products are rich in micronutrients, such as vitamins (C, D, B6, B12) and minerals (calcium, zinc, selenium) [ 5 , 59 ], all of which are relevant to the brain development and function [ 60 ]. Our findings support this conclusion, because adolescents who included dairy in breakfast had greater global cognitive performance results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different studies observed that skipping breakfast also had reduced intakes of many nutrients, like vitamins, minerals, or dietary fiber [7,8], and a high prevalence of nutrient inadequacy [9]. In agreement with this, previous systematic review and meta-analysis observed that skipping breakfast was associated with worse macronutrient intake and lower micronutrient intake [3,4].…”
Section: Introductionmentioning
confidence: 52%
“…Recent systematic reviews and meta-analyses observed that breakfast consumption was associated with better daily macro-and micronutrient intake in children and adolescents. [3,4]. It has been reported that children and adolescents who ate breakfast regularly had a healthier food pattern compared with breakfast skippers [5].…”
Section: Introductionmentioning
confidence: 99%